Identification of L-shaped curve association between serum bicarbonate concentrations and short-term outcomes in patients with acute kidney injury: a retrospective cohort study - Lu Huang; Fengying Wang (Renal Failure)
Objective This study aims to investigate the association between serum bicarbonate levels and short-term outcomes in patients with acute kidney injury (AKI), with a focus on 14-day mortality and AKI progression within a 14-day period.Methods We conducted a secondary analysis using data from the Electronic Alerts for Acute Kidney Injury Amelioration (ELAIA) study. Serum bicarbonate levels and their associated outcomes were collected for all participants. Cox regression analysis and smooth curve fitting methods were employed to achieve the research objectives.Results A total of 5,835 patients with AKI were included in the study. After adjustment for confounding factors, patients with serum bicarbonate concentrations below 22 mmol/L had a higher risk of both 14-day mortality and AKI progression compared to those with levels between 22 and 26 mmol/L (hazard ratio [HR] 1.90; 95% confidence interval [CI], 1.51–1.83 for mortality and HR 1.45; 95% CI, 1.23–1.71 for AKI progression, respectively). In contrast, patients with bicarbonate concentrations above 26 mmol/L had a lower risk of 14-day mortality (HR 0.70; 95% CI, 0.53–0.94) and AKI progression (HR 0.90; 95% CI, 0.74–1.10). Subsequent exploratory subgroup analyses revealed no statistically significant interactions (all p-values for interaction > 0.05) between 14-day mortality and serum bicarbonate levels.Conclusions In this cohort of AKI patients, serum bicarbonate concentrations below 22 mmol/L were associated with increased risks of 14-day mortality and AKI progression, while concentrations above 26 mmol/L were linked to a reduced risk of 14-day mortality.